Crystalline silicon surface passivation investigated by thermal atomic-layer-deposited aluminum oxide - 侯彩霞 郑新和 贾锐 陶科 刘三姐 姜帅 张鹏飞 孙恒超 李永涛 (Chinese physics B, 2017)
Atomic-layer-deposited（ALD） aluminum oxide（Al2O3） has demonstrated an excellent surface passivation for crystalline silicon（c-Si） surfaces, as well as for highly boron-doped c-Si surfaces. In this paper, water-based thermal atomic layer deposition of Al2O3 films are fabricated for c-Si surface passivation. The influence of deposition conditions on the passivation quality is investigated. The results show that the excellent passivation on n-type c-Si can be achieved at a low thermal budget of 250℃ given a gas pressure of 0.15 Torr. The thickness-dependence of surface passivation indicates that the effective minority carrier lifetime increases drastically when the thickness of Al2O3 is larger than 10 nm. The influence of thermal post annealing treatments is also studied. Comparable carrier lifetime is achieved when Al2O3 sample is annealed for 15 min in forming gas in a temperature range from 400℃ to 450℃. In addition, the passivation quality can be further improved when a thin PECVD-SiNx cap layer is prepared on Al2O3, and an effective minority carrier lifetime of2.8 ms and implied Voc of 721 mV are obtained. In addition, several novel methods are proposed to restrain blistering.